Introducing Vertical Policy Coordination to Comparative Policy Analysis: The Missing Link between Policy Production and Implementation. Issue 5 (20th October 2019) - Adam, Christian; Hurka, Steffen; Knill, Christoph; Peters, B. Guy; Steinebach, Yves
Abstract: The lack of effective vertical policy coordination between the policy makers at the "top" and the implementers at the "bottom" is an important source of deficits in both policy design and policy implementation. Yet while the link between policy production and implementation seems vital to explain and prevent policy failure, so far the conceptual tools to assess and compare systematically the barriers to effective vertical coordination are lacking. This paper attempts to address this gap by adopting a "transaction cost perspective" and proposing a novel concept to assess and compare the difficulty of vertical policy coordination between different policy sectors and countries.